2022
DOI: 10.1136/bmjopen-2022-061803
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and behaviour of general practitioners in Shanghai during the pandemic of COVID-19: a cross-sectional study

Abstract: ObjectivesTo understand the knowledge, attitude and behaviour of general practitioners (GPs) towards COVID-19 and to provide evidence for improved prevention and control measures against the pandemic.Study designA cross-sectional study was conducted with 1018 GPs in Shanghai from 21 February to 2 March 2020 using the WeChat platform.MethodsStratified random cluster sampling was performed according to the regional division of urban, urban–rural fringe and rural areas. This study used a self-designed mobile ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…A study from Nigeria, however, discovered that older healthcare workers had more negative attitudes toward COVID-19 prevention and control [39]. While studies from Saudi Arabia, Sierra Leone, and Jordan also discovered that male healthcare workers, like the male GPs from Bosnia and Herzegovina in this study, had more positive attitudes toward COVID-19 prevention and control [15,32,38], another study from Saudi Arabia, and studies from India and China, contrary to the results among the Bosnian GPs in this study, showed that females had more positive attitudes than males [19,34,43]. Finally, a study that included GPs from the United States, Turkey, and Greece and another study that included only GPs from Greece found no connection between gender and attitudes toward COVID-19 prevention and control [7,29].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…A study from Nigeria, however, discovered that older healthcare workers had more negative attitudes toward COVID-19 prevention and control [39]. While studies from Saudi Arabia, Sierra Leone, and Jordan also discovered that male healthcare workers, like the male GPs from Bosnia and Herzegovina in this study, had more positive attitudes toward COVID-19 prevention and control [15,32,38], another study from Saudi Arabia, and studies from India and China, contrary to the results among the Bosnian GPs in this study, showed that females had more positive attitudes than males [19,34,43]. Finally, a study that included GPs from the United States, Turkey, and Greece and another study that included only GPs from Greece found no connection between gender and attitudes toward COVID-19 prevention and control [7,29].…”
Section: Discussioncontrasting
confidence: 90%
“…Considering age, a study conducted in India showed that, like the Croatian GPs in this study, older healthcare workers from this country more frequently displayed positive practices regarding COVID-19 prevention and control in comparison to their younger colleagues [19]. Furthermore, like the Croatian GPs in this study, a study from China showed that female GPs expressed more positive practices regarding COVID-19 prevention and control [43], while a study in Saudi Arabia discovered that male GPs from Saudi Arabia were more likely to comply with appropriate practices regarding COVID-19 prevention and control in comparison to their female colleagues [34]. Unlike the Croatian GPs in this study, studies in Riyadh, Saudi Arabia, and India revealed that single healthcare workers more frequently displayed positive practices regarding COVID-19 prevention and control in comparison to their married colleagues [19,23].…”
Section: Discussionmentioning
confidence: 48%
“…At present, the COVID-19 prevention and control situation is improving on the whole, but we should not be complacent. There have been studies on COVID-19 related groups such as students and medical staffs ( 7 , 8 ), Wu’s study on in-hospital patients, and the research shows that in-hospital patients’ awareness of prevention and control is positively correlated with their knowledge and attitude ( 9 ), Tang et al ’s survey of general practitioners suggests that effective knowledge training can improve the prevention and control of COVID-19 ( 10 ). However, people living in remote mountainous areas are less concerned.…”
Section: Introductionmentioning
confidence: 99%